Effects of climate change on the steric height and heat content in the Ballenas Channel, Gulf of California, Mexico (1939–2011). (September 2022) - Serrano, David; Ramírez-Félix, Evlin; Hendrickx, Michel; Delgadillo-Hinojosa, Francisco
Highlights: The steric height rates were with a positive trend for the 200–1000 m, 500–1000 m and 700–1000 m layers. The heat content rates for the same layers were positive with a clear tendency to decrease with depth. The steric height in the water column below 700 m can contribute with ∼40%. The heat content indicates that seas located below mid-latitudes are less susceptible to climate change compared to seas located at high latitudes. Abstract: The steric height ( StH ) and heat content ( HC ) are the integral variables most used as a measure of change of sea level at global scale. This study was carried out based on six data sets of average temperature and salinity profiles collected during the years 1939, 1962, 1974, 1984, 2003 and 2011 along the Ballenas Channel in the northern section of the Gulf of California. In order to eliminate high frequency thermal variability and evaluate its contribution in deep layers, StH and HC were calculated for the columns of 0–1000 m, 200–1000 m, 500–1000 m and 700–1000 m. We estimated StH rates of 1.0 ± 0.18 mm year −1, 0.54 ± 0.14 mm year −1 and 0.30 ± 0.11 mm year −1 for the 200–1000 m, 500–1000 m and 700–1000 m columns, respectively. In particular, the contribution of the 700–1000 m column ranged from 15% in 1984 to 37% in 2011. We also found that the increase in HC in 72 years for the column of 200–1000 m was 1.6 × 10 9 Jm −2 representing an average net heating rate of 0.7 W m −2 . As a comparison, the average net heating rate in the Greenland Sea was 5.9 W m −2 for 13 years. This result may indicate that the marginal seas located below mid-latitudes could be less susceptible to the effects of climate change.